Media Virtual Tour Tembang Macapat Berbantuan Millealab untuk Meningkatkan Motivasi Belajar Siswa - Diva Fikri Harry Adnan; Cepi Riyana; Ahmad Fajar Fadlillah (Prodi Pendidikan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2024)
This research is based on the problem of low student motivation in learning Tembang Macapat due to monotonous learning methods. The purpose of this study is to examine the effect of virtual tour media assisted by Millealab on student motivation in cognitive aspects, self-appearance, and self-improvement on Tembang Macapat material. By applying the quasi-experimental method of nonequivalent control group design, two 9th grade classes at SMPN 2 Majenang were selected as samples for the experimental and control groups. A questionnaire was chosen as the research instrument to collect pretest and posttest data. The data collected were analyzed with the normality test of Shapiro-Wilk technique, homogeneity test of Levene's Test technique, and hypothesis testing with independent sample t-test technique. The findings showed that the use of virtual tour media assisted by Millealab had a significant effect in increasing students' learning motivation on Tembang Macapat material. This can be seen from the higher score increase in the experimental group, compared to the control group and has been proven in hypothesis testing. The conclusion of this study is that ninth grade students at SMP Negeri 2 Majenang are more motivated in learning Tembang Macapat material because of the use of virtual tour media assisted by Millealab. The implication of this research is that the use of virtual tour media assisted by Millealab can be an innovative and effective learning alternative for teachers in fostering learning motivation.